Correction: House dust mites in three contrasting climatic regions of Saudi Arabia - Riyadh Hussain S. Aeban; Medjedline Hani; Henk R. Braig; M. Alejandra Perotti (Experimental and Applied Acarology, 2026)

House dust mites in three contrasting climatic regions of Saudi Arabia - Riyadh Hussain S. Aeban; Medjedline Hani; Henk R. Braig; M. Alejandra Perotti (Experimental and Applied Acarology, 2026)
Just a handful of mite species are suspected inhabiting the dust of houses within arid areas of the Arabian Peninsula. In this study, we identified and compared the house dust mite diversity in three different climatic areas within Saudi Arabia. Sampling was carried out over one year and two months, with samples collected in the desert, the coast, and in the highlands. It reviews all known mites of house dust of Saudi Arabia. A total of 998 mites were collected belonging to 23 species in 14 families. Pyroglyphidae (Astigmata) were the most abundant. The interaction among pyroglyphid species in the climatic regions was analysed. While variation in abundance of Pyroglyphidae among regions was weak, there was a strong desert region Cheyletus eruditus – Dermatophagoides farinae association, perhaps explaining that D. farinae populations from the desert have become C. eruditus’ favourite prey. Another interesting association is that of Pyroglyphidae with Acaridae. D. pteronyssinus shows significant numerical dominance in the highlands. A newly discovered species of Dermatophagoides did not interact with any of the other 2 species and was restricted to the coastal region. Dermatophagoides n. sp. and Cheletopsis sp. can be used as markers of location in forensic analyses (provenance), based on their unique association with the coast and desert, respectively. A new species of Dermatophagoides has been identified. Five species are new to Saudi Arabia and the Arabian Peninsula including house dust, ten species are new to the house dust mite fauna of Saudi Arabia and the Arabian Peninsula but have been recorded as storage mites, totalling 15 new house dust mites for the Arabian Peninsula. Two species are new to house dust in Saudi Arabia, but already known from house dust in Kuwait. Of the fifteen new house dust mites for the Arabian Peninsula, five species are new to the dust mite fauna worldwide: Prostigmata: Cheletopsis sp. (Cheyletidae); Mesostigmata: Proctolaelaps pygmaeus (Melicharidae), Macrocheles muscaedomesticae (Macrochelidae); and Oribatida: Oribatula tibialis (Oribatulidae), and Ceratozetes sp. (Ceratozetidae).

The TAP-IVS-EPSPS glyphosate resistance mutation evolved in Amaranthus hybridus exhibits an adaptation cost in a glyphosate free environment - Valeria E. Perotti; Valeria E. Palmieri; Axl Graves; Analía I. Menéndez; Cecilia Casas; Hugo R. Permingeat; Martin M. Vila-Aiub (Plant Science, 2025)

Assessing the effect of acute exposure to predator risk in amphibians at different temperatures. An oxidative stress approach in tadpoles - M. G. Perotti; R. Ghirardi; D. Miloch; J. Cazenave (Hydrobiologia, 2025)

Impact of the use of skim milk powder and adjunct cultures on the levels of organic acid and carbohydrates, volatile compounds and sensory properties of Cremoso cheese - Paula Giménez; Guillermo H. Peralta; Mara E. Batistela; Facundo Cuffia; Elisa C. Ale; I. Verónica Wolf; M. Cristina Perotti; Erica R. Hynes; Carina V. Bergamini (International Dairy Journal, 2023)

Structural and morphological properties of in-situ biosynthesis of biocompatible bacterial cellulose/Laponite nanocomposites - Rafael R. Domeneguetti; Vanessa Y. Sakai; Gustavo F. Perotti; Isabel C. Silva; Agnieszka Tercjak; Hernane S. Barud; Fernando Pavan; Vera R.L. Constantino; Sidney J. Ribeiro (Applied Clay Science, 2023)

Mapping soil liquefaction susceptibility across Europe using the analytic hierarchy process - C. Meisina; R. Bonì; F. Bozzoni; D. Conca; Cesare Perotti; Pina Persichillo; C. G. Lai (Bulletin of Earthquake Engineering, 2022)
Mapping the susceptibility of earthquake-induced soil liquefaction at the continental scale is a challenge. Susceptibility of soils to liquefaction is the tendency of certain geomaterials to undergo a severe stiffness degradation and loss of shear strength. The latter could be induced by cyclic loading induced by seismic events. The liquefaction surface evidence is a local phenomenon, and detailed geotechnical field investigations are not available for regional studies, not to mention at continental scales. The literature review shows earthquake-induced soil liquefaction evidence in several European countries, yet, a comprehensive picture of the susceptibility at the European scale is not available. This work aims to develop a methodology to assess the earthquake-induced soil liquefaction susceptibility in Europe using geospatial parameters weighted via the Analytic Hierarchy Process (AHP). The major outcome of the study is a novel Liquefaction Susceptibility map of Europe (LSE), based on the building of ten different European macro-units for earthquake-induced soil liquefaction. These European macro-units have been delineated in this work in order to be homogenous areas from the geological, physiographical, and geomorphological points of view. The adopted input parameters are the depositional environment of the sediments, the distance from water bodies (coast and rivers), and the compound topographic index (as a proxy of the soil saturation). The resolution of the LSE map is 900 × 900 m. The results have been cross-compared with soil liquefaction susceptibility maps available for a region of Greece (i.e. Thrace), Portugal, Bulgaria, and sites where liquefaction manifestations occurred across Europe. The LSE can be adopted to identify at large scale the areas susceptible to liquefaction including also the territories across Europe characterized by low seismicity and potentially affected by anthropogenic seismicity.

Assessment of the bioprotective potential of lactic acid bacteria against Listeria monocytogenes in ground beef - Johana S. Gomez; Romina B. Parada; Marisol Vallejo; Emilio R. Marguet; Augusto Bellomio; Nora Perotti; Kátia G. de Carvalho (Archives of Microbiology, 2021)

Molecular Mechanisms Endowing Cross-resistance to ALS-Inhibiting Herbicides in Amaranthus hybridus from Argentina - Alvaro S. Larran; Florencia Lorenzetti; Daniel Tuesca; Valeria E. Perotti; Hugo R. Permingeat (Plant Molecular Biology Reporter, 2018)

Macrocheles species (Acari: Macrochelidae) associated with human corpses in Europe - Naila A. Che Kamaruzaman; Peter Mašán; Yelitza Velásquez; Alejandro González-Medina; Anders Lindström; Henk R. Braig; M. Alejandra Perotti (Experimental and Applied Acarology, 2018)

Assessment of cryopreserved donor skin viability: the experience of the regional tissue bank of Siena - E. Pianigiani; L. Tognetti; F. Ierardi; G. Mariotti; P. Rubegni; G. Cevenini; R. Perotti; M. Fimiani (Cell and Tissue Banking, 2016)

The transition between the two major Permian tectono-stratigraphic cycles in the central Southern Alps: results from facies analysis and U/Pb geochronology - Nicola Gretter; Ausonio Ronchi; Antonio Langone; Cesare R. Perotti (International Journal of Earth Sciences, 2013)

Intertribal hybrid plants produced from crossing Arabidopsis thaliana with apomictic Boechera - Allan R. Lohe; Enrico Perotti (Planta, 2012)

Permian continental basins in the Southern Alps (Italy) and peri-mediterranean correlations - Giuseppe Cassinis; Cesare R. Perotti; Ausonio Ronchi (International Journal of Earth Sciences, 2012)

Potential distribution of Batrachochytrium dendrobatidis in Argentina: implications in amphibian conservation - R. Ghirardi; M. G. Perotti; M. M. Steciow; M. L. Arellano; G. S. Natale (Hydrobiologia, 2011)

Carcases and mites - Henk R. Braig; M. Alejandra Perotti (Experimental and Applied Acarology, 2009)

Forensic acarology: an introduction - M. Alejandra Perotti; M. Lee Goff; Anne S. Baker; Bryan D. Turner; Henk R. Braig (Experimental and Applied Acarology, 2009)

Phoretic mites associated with animal and human decomposition - M. Alejandra Perotti; Henk R. Braig (Experimental and Applied Acarology, 2009)

Tectonic and sedimentary evolution of the Lower Pliocene Periadriatic foredeep in Central Italy - Stefano Carruba; Raffaele Casnedi; Cesare R. Perotti; Milly Tornaghi; Giorgio Bolis (International Journal of Earth Sciences, 2006)